Renewal of Islamic Studies Approach From Above: The Growth and Development of Religious Teacher Thought in Contemporary Indonesia - Ulum, Miftahul; Romlah, Siti; Fadhilah, Rifqi Zaidan; Mahmudah, Mahmudah; Muazzaroh, Faizatul; Habib, Muhammad Alhada Fuadilah; Binmong, Sorhibulbahree (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2024)
The Religious Teachers Education Program is a forum for guidance that is held to provide debriefing and at a time increasing the mastery of the material of a religious teacher, especially in religious knowledge scope. Data analysis was carried out namely during the study and after the study was conducted. The results showed that the education program of the religious teachers was held every day at 16.00-17.00. The form of the implementation is the same as the teaching and learning process carried out in the classes usually. The method commonly used is the lecture and question and answer methods. And the study material covers 8 fields of science, which is ushūl sciences (the book of Jawẖaroh at-Tauẖīd), furu sciences (the book of Fatul al-Qarīb), tafsīr (the book of Tafsīr Jalalain), hadits (the book of Riyad as-Sholiẖīn), tools sciences (the book of Ibn Aqīl), the qushos sciences (the book of Daqoiqul Akhbar), Sufi sciences (the book of Bidāyatul Hidāyah), moral sciences (the book of Ta'līmul Muta'allīm and Uqudul Lujain). Constraints faced in the implementation of the Religious Teacher Education program on the development of Religious teachers competencies i.e. lack of interesting or willingness of the asatidz to consistently participate in the program with the excuse of being lazy or busy working, inadequate time, social activities such tahlilan. Efforts made in overcoming obstacles are by providing stabilization and convincing the asatidz of the importance of participating in the program of the education of the religious teachers to increase and expand mastery of the material to be delivered to his students. In addition, the madrasah head also provides allowances.